Assessment Experience from 'Nutrition Project Implementation of BRAC Nutrition, Which Subsequently Contributed to Social Impact. - Islam, Monirul. (Tufts University. Tisch Library., 2020)
This poster shows the assessment experience from nutrition project implementation of BRAC nutrition.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy